When soldiers fall : how Americans have confronted combat losses from World War I to Afghanistan - Casey, Steven (Oxford University Press, 2013)
Call it the Vietnam Syndrome or Black Hawk Down blowback. It's the standard assumption that Americans won't tolerate combat casualties, that a rising body count lowers support for war. But that's not true, argues historian Steven Casey; even worse, this assumption damages democracy. Fearing a backlash, the military has routinely distorted its casualty reports in order to hide the true cost of war. When Soldiers Fall takes a new look at the way Americans have dealt with the toll of armed conflict. Drawing on a vast array of sources, from George Patton's command papers to previously untapped New.